Spark plasma sintered Ni-YSZ/YSZ bi-layers for solid oxide fuel cell - Bezdorozhev, Oleksii (2014)
Ni-YSZ/YSZ bi-layers for SOFCs were fabricated by spark plasma sintering (SPS). Optimization of SPS parameters of YSZ and NiO/YSZ powders was performed in order to fabricate anode and electrolyte with desired microstructures. The effect of sintering conditions on microstructure and electrical properties of YSZ was studied. The influence of processing parameters and amount of pore-forming agent on the microstructures of Ni/YSZ cermets was also investigated. It was shown that the amount of pore-former and in situ reduction of nickel oxide had a substantial effect on microstructure of the cermets. The in situ reduced anode demonstrates sufficiently homogeneous distribution of Ni and YSZ making a conduction path for electrons and ions. Ni-YSZ/YSZ bi-layers with crack-free and well-bonded anode/electrolyte interface were obtained. Furthermore, warping was not observed for the produced bi-layers.